Differentiation Between Paraclinoid and Cavernous Sinus Aneurysms with Contrast-Enhanced 3D Constructive Interference in Steady- State MR Imaging - Hirai, T.; Kai, Y.; Morioka, M.; Yano, S.; Kitajima, M.; Fukuoka, H.; Sasao, A.; Murakami, R.; Nakayama, Y.; Awai, K.; Toya, R.; Akter, M.; et al. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Differentiation between paraclinoid and cavernous sinus aneurysms of the internal carotid artery (ICA) is critical when considering treatment options. The purpose of this study was to determine whether contrast-enhanced (CE) 3D constructive interference in steady state (CISS) MR imaging is useful to differentiate between paraclinoid and cavernous sinus aneurysms.MATERIALS AND METHODS: This study included 11 aneurysms in 10 consecutive female patients, ranging from 52 to 66 years of age. All aneurysms were adjacent to the anterior clinoid process. After conventional and CE 3D-CISS imaging on a 1.5T MR imaging unit, all patients underwent surgery, and the relationship between the aneurysms and the dura was confirmed. Two neuroradiologists evaluated the location of the aneurysms on CE 3D-CISS images and classified them as intradural, partially intradural, and extradural aneurysms. Operative findings were used as a reference standard. To understand the imaging characteristics, we assessed the boundary and signal intensity of the cavernous sinus, CSF, and carotid artery on the side contralateral to the lesion.RESULTS: Operative findings disclosed that 5 aneurysms were intradural and 6 were extradural. All except 2 were accurately assessed with CE 3D-CISS imaging. One intradural aneurysm adjacent to a large cavernous aneurysm and 1 cavernous giant aneurysm were assessed as partially intradural. On CE 3D-CISS images, the boundary between the CSF, cavernous sinus, and carotid artery was identified by high signal-intensity contrast in all cases.CONCLUSION: CE 3D-CISS MR imaging is useful for the differentiation between paraclinoid and cavernous sinus aneurysms.